Global Metabolomics Reveals the Metabolic Dysfunction in Ox-LDL Induced Macrophage-Derived Foam Cells - Xu, Wenjuan; Wei, Ziyi; Dong, Jiaojiao; Duan, Feipeng; Chen, Kuikui; Chen, Chang; Liu, Jie; Yang, Xiaowei; Chen, Lianming; Xiao, Hongbin; Liu, An (Frontiers in Pharmacology, 2017)
Atherosclerosis (AS) is a chronic disorder of large arteries that is a major risk factors of high morbidity and mortality. Oxidative modification LDL is one of the important contributors to atherogenesis. Macrophages take up ox-LDL and convert into foam cells, which is the hallmark of atherosclerosis. To advance the understanding of the metabolic perturbation involved in ox-LDL induced macrophage-derived foam cells and discover the potential biomarkers of early atherosclerosis, a global metabolomics approach was applied based on UHPLC-QTOF/MS. Multivariate statistical analyses identified five metabolites (25-azacholesterol, anandamide, glycocholate, oleoyl ethanolamide and 3-oxo-4, 6-choladienoate) for distinguishing foamy macrophages from controls. Among the six main metabolic pathways, the unsaturated fatty acid, especially arachidonic acid metabolism, contributed importantly to early atherosclerosis. A new biomarker, anandamide (AEA), whose “on-demand” synthesis and metabolism in macrophages are disturbed by overloaded ox-LDL, results in metabolic obstruction. This study is the first to investigate the metabolic disturbance in macrophage-derived foam cells induced by ox-LDL and screen potential biomarkers and metabolic pathways associated with early atherosclerosis. Our findings provide a new insight in the underlying pathophysiological mechanisms and also help to identify novel targets for the intervention of atherosclerosis.